ASEAN Single Window Implementation: Exploring Benefits, Challenges, Solutions, and Future Roadmap - Akbar, Syahrir; Mendoza, Muhammad Wafiq; Febriansyah (Scimadly Publishing, 2025)
The rapid globalization of trade demands more efficient cross-border processes, yet ASEAN countries still face high logistics costs and procedural delays. As a response, the ASEAN Single Window (ASW) initiative was developed to streamline customs processes and integrate trade administration systems across member states. This study aims to evaluate the benefits of ASW implementation, identify key challenges across political, economic, social, technological, environmental, and legal dimensions (PESTEL), and offer strategic recommendations for improvement. The research uses a qualitative method based on secondary data, including journal articles, official reports, and policy documents published between 2015-2025. PESTEL analysis is applied to structure and assess the external factors influencing ASW implementation. Findings show that ASW significantly improves trade efficiency, transparency, and cost-effectiveness. However, challenges such as regulatory inconsistencies, technological gaps, and limited legal harmonization persist. The study outlines short-, medium-, and long-term roadmaps, offering phased solutions such as modular system design, AI-based risk prediction, and legal standardization. In conclusion, ASW holds strong potential to enhance ASEAN’s regional trade competitiveness if implementation is supported by political commitment, legal reform, capacity-building, and robust digital infrastructure.